Saikosaponin A alleviates depressive-like behavior induced by reserpine in mice by regulating gut microflora and inflammatory responses - Menglin Wang; Haojun Li; Wenjing Zhang; Li Zhang; Shun Wang; Miao Jia; Lu Jia; Yu Zhang; Haifei Gao; Xianwu Zhang; Zhaohui Yin (PLoS ONE, 2025)
Saikosaponin A (SSA), a key ingredient of Chaihu-Shugan-San, has been shown to possess anti-inflammatory, antioxidant and antidepressant properties. Therefore, the present study aimed to investigate the potential mechanism of action and the effect of SSA on reserpine-induced depressive-like symptoms in mice. Establishing mouse model of depression using intraperitoneal injection of reserpine (RSP). Forced swimming test, tail suspension test and sucrose preference test were used to assess depression-like behavior in mice. The results showed that mice exposed to RSP not only showed weight loss and depressive behavior, but also elevated levels of IL-1β and TNF-α, as well as upregulated levels of reactive oxygen species (ROS) and lipid peroxides in the hippocampus. Detection of changes in the intestinal flora of mice using 16S rRNA, it was observed that the intestinal flora changed following SSA treatment. Not only was there an increase in the overall abundance of the intestinal microbiota, but there was also a significant down-regulation of the Firmicutes and an up-regulation of the Verrucomicrobia at the phylum level. Furthermore, SSA treatment markedly improved depressive-like behavior induced by RSP, alleviated damage to the hippocampus, elevated levels of monoamine neurotransmitters, suppressed inflammatory factors in the hippocampus, reduced hippocampal oxidative stress, and restored gut microbiota disruption in RSP-induced mice. The findings propose that SSA has the potential to alleviate depressive symptoms in mice by enhancing monoamine neurotransmitter levels, suppressing hippocampal inflammation, and modifying gut microbial composition.